Exercise as an Intervention for the Age-Related Decline in Neural Metabolic Support - Anderson, Brenda J.; Greenwood, Shayri J.; McCloskey, Daniel P. (Frontiers in Aging Neuroscience, 2010)
To identify interventions for brain aging, we must first identify the processes in which we hope to intervene. Brain aging is a period of decreasing functional capacity and increasing vulnerability, which reflect a reduction in morphological organization and perhaps degeneration. Since life is ultimately dependent upon the ability to maintain cellular organization through metabolism, this review explores evidence for a decline in neural metabolic support during aging, which includes a reduction in whole brain cerebral blood flow, and cellular metabolic capacity. Capillary density may also decrease with age, although the results are less clear. Exercise may be a highly effective intervention for brain aging, because it improves the cardiovascular system as a whole, and increases regional capillary density and neuronal metabolic capacity. Although the evidence is strongest for motor regions, more work may yield additional evidence for exercise-related improvement in metabolic support in non-motor regions. The protective effects of exercise may be specific to brain region and the type of insult. For example, exercise protects striatal cells from ischemia, but it produces mixed results after hippocampal seizures. Exercise can improve metabolic support and bioenergetic capacity in adult animals, but it remains to be determined whether it has similar effects in aging animals. What is clear is that exercise can influence the multiple levels of support necessary for maintaining optimal neuronal function, which is unique among proposed interventions for aging.